2005
DOI: 10.1038/ng1557
|View full text |Cite
|
Sign up to set email alerts
|

A functional SNP in CILP, encoding cartilage intermediate layer protein, is associated with susceptibility to lumbar disc disease

Abstract: Lumbar disc disease (LDD) is caused by degeneration of intervertebral discs of the lumbar spine. One of the most common musculoskeletal disorders, LDD has strong genetic determinants. Using a case-control association study, we identified a functional SNP (1184T --> C, resulting in the amino acid substitution I395T) in CILP, which encodes the cartilage intermediate layer protein, that acts as a modulator of LDD susceptibility. CILP was expressed abundantly in intervertebral discs, and its expression increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
200
1
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(208 citation statements)
references
References 29 publications
4
200
1
3
Order By: Relevance
“…Several studies have found familial predisposition to LDD, including early onset sciatica and lumbar disc herniation. In addition, mutations or polymorphisms in several genes have been reported to be associated with either the presence or severity of disc degeneration, including gene coding for collagen IX and XI [2,12,13], aggrecan [9], cartilage intermediate layer protein [18], vitamin D receptor [22], interleukin-1 [19], matrix metalloproteinase-3(MMP-3) [20], tissue inhibitor of metalloproteinase-1(TIMP-1) [21], and cyclooxygenase-2 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found familial predisposition to LDD, including early onset sciatica and lumbar disc herniation. In addition, mutations or polymorphisms in several genes have been reported to be associated with either the presence or severity of disc degeneration, including gene coding for collagen IX and XI [2,12,13], aggrecan [9], cartilage intermediate layer protein [18], vitamin D receptor [22], interleukin-1 [19], matrix metalloproteinase-3(MMP-3) [20], tissue inhibitor of metalloproteinase-1(TIMP-1) [21], and cyclooxygenase-2 [21].…”
Section: Introductionmentioning
confidence: 99%
“…1 Individual genes associated with disc degeneration include those for collagen type IX, 91 aggrecan, 92 vitamin D receptor, 93 MMP3, 94 and cartilage intermediate layer protein. 95 The products of these genes probably affect the strength of skeletal tissues, and their systemic effects may explain why disc degeneration is more prevalent in those with osteoarthritis. 74 Environmental risk factors for disc degeneration include high and repetitive mechanical loading 1,96 and smoking cigarettes.…”
Section: Disc Degeneration: Epidemiologymentioning
confidence: 99%
“…CILP was originally isolated from human articular cartilage, is a large secreted glycoprotein, and is thought to play a role in cartilage scaffolding (6). CILP has been associated with osteoarthritis (12)(13)(14), and more recently with lumbar disc disease in a Japanese population (8), and will be referred to hereafter as CILP1 (5). We and others have shown CILP-1 and CILP-2 to be structurally similar (5) (supplemental Fig.…”
Section: Identification Of Differential Expression Of Cilp2 In Articularmentioning
confidence: 99%
“…CILP-1 levels have been shown to increase with age (6,10) and in patients with early stage osteoarthritis (11). The association of single nucleotide polymorphisms in the CILP1 gene with musculoskeletal disorders including osteoarthritis (12)(13)(14), and lumbar disc disease in a Japanese population (8) implies that CILP proteins may be important in cartilage structure and disease. In contrast to CILP-1, little is known about the mRNA and protein expression of CILP-2 in cartilage and noncartilaginous tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation